What is a person‐centred approach? Familiarity and understanding of individualised funding amongst carers in New South Wales. Issue 3 (October 2014) - Broady, Timothy
Abstract : Person‐centred approaches place individuals with a disability at the centre of decision making, with their carers and family invited to be partners in the process. Rather than being required to fit within existing service programs, person‐centred approaches enable individuals to choose the support options that best meet their needs. In order to facilitate this, person‐centred approaches will be accompanied by the introduction of individualised funding. This means the individual will be provided with funding to purchase services of their choosing. Given these significant changes occurring in the disability sector, Carers NSW surveyed informal carers of people with a disability to identify what they knew about person‐centred approaches and how they felt about their introduction. Survey results indicate that there is a need to increase the capacity and willingness of carers significantly in order to engage with person‐centred approaches and individualised funding. Carers require targeted and comprehensive information about these concepts in order to understand fully the changes occurring within the disability sector. These findings also indicate specific areas that need to be addressed in order to increase carers' awareness of these concepts and also to address existing negativity and confusion.